Advances in Precision Medicine Oncology - Arnouk, Hilal; Abdul Rasool Hassan, Bassam; Arnouk, Hilal; Abdul Rasool Hassan, Bassam (IntechOpen, 2021)
Recent advances in precision medicine and immuno-oncology have led to highly specific and efficacious cancer therapies such as monoclonal antibodies and immune checkpoint inhibitors (ICIs). This book provides an up-to-date overview of advances in the field of immuno-oncology. Chapters cover such topics as ICIs and how they mount a robust immune response against cancer cells as well as the response of ICIs to treatment predictive biomarkers and their potential immune-related adverse events (irAEs). Additionally, the book includes a comprehensive review of the powerful FDA-approved therapeutic agent doxorubicin, highlighting the molecular mechanisms behind doxorubicin's drug resistance and critical side effects.
English
Keywords: Oncology